(untitled) (Journal of Computational Mathematics, 1995)
In this paper the problems to determine an inconsistent system of linear inequalities and to correct its right-hand side vector are solved by using the isometric plane method for linear programming. As an example, the suitable perturbation quantity of the perturbed inequalities of ill-conditioned linear equations is determined in the numerical experiments.